Role of grit as mediator in the relationship of openness to experience and effectiveness of teachers during distance learning - Salim, Rose Mini Agoes; Prastyo, Aqilla Sekar Ningrum; Rumalutur, Nur Aisyah; Situmorang, Dominikus David Biondi (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
The transition from offline to online learning is a challenge for teachers in effectively fulfilling their roles and necessitates openness and adaptability to change. Therefore, this study aimed to investigate the role of grit as a mediator in the relationship between openness to experience and the effectiveness of teachers. This was carried out during distance learning among 211 vocational high school teachers in DKI Jakarta. The results showed significant indirect (ab = .321, p < .01, 95% CI [.177, .487]) and direct effects (c’ = 1.298, p < .01, 95% CI [.964, 1.633]). These results indicated that grit partially mediated the relationship between openness to experience and the effectiveness of teachers. Consequently, the study implied that fostering a high level of openness to experience enhanced grit and increased teachers' effectiveness.